An overview of a leader journal in the field of transport: a bibliometric analysis of “Computer-Aided Civil and Infrastructure Engineering” from 2000 to 2019 - Wang, Xinxin; Xu, Zeshui; Ge, Zijing; Zavadskas, Edmundas Kazimieras; Skačkauskas, Paulius (Transport, 2020)
Computer-Aided Civil And Infrastructure Engineering (CACAIE) is an international journal, and the first documents was published from 1980. This article is to make an overview based on bibliometric analysis to celebrate the 35th anniversary of CACAIE till 2019. At present, 1045 publications can be indexed in the Clarivate Analytics Web of Science (WoS) from 2000 to 2019, and we explore the characteristics of these publications by bibliometric methods and tools (VOSviewer and CiteSpace). First, the fundamental information of publications is given with the help of some bibliometric indicators, such as the number of citations and h-index. According to high-citing and high-cited publications, we analyse that who pays closer attention to the journal and what the journal most focuses on considering sources, countries/regions, institutions and authors. After that, the influential countries/regions and references are presented, and collaboration networks are given to show the relationship among countries/regions, institutions and authors. In order to understand the development trends and hot topics, co-occurrence analysis and timeline view of keywords are made to be visual. In addition, publications in four fields – Construction & Building Technology; Engineering, Civil; Transportation Science & Technology; Computer Science, Interdisciplinary Applications – that CACAIE refers are summarized, and further discussions are made for the journal and scholars. Finally, some main findings are concluded according to all analysis. This article provides a certain reference for scholars and journals to further research and promote the scientific-technological progress. First published online 6 January 2021